Impact of Phytochemicals on PPAR Receptors: Implications for Disease Treatments - Ayesheh Enayati; Mobina Ghojoghnejad; Basil D. Roufogalis; Seyed Adel Maollem; Amirhossein Sahebkar (PPAR Research)
Peroxisome proliferator-activated receptors (PPARs) are members of the ligand-dependent nuclear receptor family. PPARs have attracted wide attention as pharmacologic mediators to manage multiple diseases and their underlying signaling targets. They mediate a broad range of specific biological activities and multiple organ toxicity, including cellular differentiation, metabolic syndrome, cancer, atherosclerosis, neurodegeneration, cardiovascular diseases, and inflammation related to their up/downstream signaling pathways. Consequently, several types of selective PPAR ligands, such as fibrates and thiazolidinediones (TZDs), have been approved as their pharmacological agonists. Despite these advances, the use of PPAR agonists is known to cause adverse effects in various systems. Conversely, some naturally occurring PPAR agonists, including polyunsaturated fatty acids and natural endogenous PPAR agonists curcumin and resveratrol, have been introduced as safe agonists as a result of their clinical evidence or preclinical experiments. This review focuses on research on plant-derived active ingredients (natural phytochemicals) as potential safe and promising PPAR agonists. Moreover, it provides a comprehensive review and critique of the role of phytochemicals in PPARs-related diseases and provides an understanding of phytochemical-mediated PPAR-dependent and -independent cascades. The findings of this research will help to define the functions of phytochemicals as potent PPAR pharmacological agonists in underlying disease mechanisms and their related complications.